Six-Year Follow-up of a Preventive Intervention for Parentally-Bereaved Youth: A Randomized Controlled Trial - Sandler, Irwin (2010)
OBJECTIVE: To evaluate efficacy of the Family Bereavement Program (FBP) to prevent mental health problems of parentally-bereaved youth and their parents six years later. DESIGN: Randomized controlled trial. SETTINGS: Arizona State University Prevention Research from 2002 to 2005. PARTICIPANTS: 218 bereaved youth (89.3% of 240 enrolled in the trial six years earlier) and 113 spousally-bereaved parents. INTERVENTIONS: FBP includes 12 group sessions for caregivers and youth; literature control (LC) condition includes bereavement books for youth and caregivers. . MAIN OUTCOME MEASURES: Compared youth in FBP and LC on a measure of mental disorder diagnosis, five measures of mental health problems and four measures of competent functioning; compared spousally-bereaved parents on two measures of mental health problems. RESULTS: Youth in FBP had significantly lower externalizing problems as reported by caregiver/youth (adjusted mean, LC = .13, FBP = −.06; p = .02) and teacher reports of externalizing problems (adjusted mean, LC = 56.27, FBP = 52.69; p = .001) and internalizing problems (adjusted mean, LC = 56.27, FBP = 47.29; p = .002) and higher self-esteem (adjusted mean, LC = 31.91, FBP = 33.93; p = .005). Parents in FBP had lower depression scores than LC (adjusted mean, LC = 7.83, FBP = 5.48; p = .04). A significant moderated program effect indicated that for youth with lower baseline problems, rate of diagnosed mental disorder was lower for FBP than LC. CONCLUSIONS: Study demonstrates efficacy of the FBP to reduce mental health problems of bereaved youth and their parents six-years later.